The Effect of Crude Oil Price Volatility on the Iraqi Fiscal Policy Response (1990-2017) - زغير, عمار نعيم; الجابري, قصي عبود فرج (Journal of Petroleum Research and Studies, 2020)
The study aims at measuring and analyzing the effect of crude oil price volatility on the Iraqi fiscal policy response (1990-2017) using NARDL model. The study found that there is a positive، non-linear، long-term relation between the volatility in the global market and the fiscal policy of Iraq for the enquiry period. It revealed that an (1%) increase in crude oil price will lead to an increase in public expenditures by (%0.650) while a (1%) decrease in crude oil price will lead to a decrease in public expenditures by (%0.628). It also revealed that a (1%) change in state revenues of Iraq will lead to a change in public expenditures by (%0.941). In addition, study found that any shock occurs in crude oil prices will lead to an increase in public expenditures of Iraq to reach its peak after one season. After the passage of six seasons since the shock started، public expenditure will be reached to equilibrium before the shock.